A cross-linguistic study of prosodic lengthening in child-directed speech - Payne, E; Post, B; Astruc, L; Prieto, P; Vanrell, M (International Speech Communication Association, 2010)
We compared the manifestation of prosodic lengthening in child-directed speech with the adult-directed speech of 6 Catalan and English women. Results showed a less variegated system of prosodic lengthening in CDS, with the selective enhancement of certain structures, notably phrasefinal lengthening and (in English) nuclear accented syllables.